Space-time adaptive processing using circular arrays. - Sarfar, Tapan K. (IEEE Antennas & propagation magazine.)
A direct data-domain (D3) least-squares space-time adaptive-processing (STAP) approach is presented for adaptively enhancing radar signals in a non-homogeneous environment of jammers, clutter, and thermal noise, utilizing a circular antenna array. The non-homogeneous environment may consist of non-stationary clutter. The D 3 approach is applied directly to the data collected by a circular antenna array (utilizing space), and in time (Doppler) diversity. Conventional STAP generally utilizes statistical methodologies, based on estimating a covariance matrix of the interference, using the data from various range cells of the circular array and assuming that it is a uniform linear array. However, for highly transient and inhomogeneous environments, the conventional statistical methodology may be difficult to apply. Moreover, the error in forming the covariance matrix by assuming that the data collected by the circular array is assumed to be a uniform linear array is highly problem dependent. Hence the D3 method is presented, as it analyzes the data in space and time over each range cell separately. However, it treats the antenna array as circular, i.e., it deals with the antenna structure in its proper form. Limited examples are presented to illustrate the application of this approach.